Advocating access to justice: facilitating or gatekeeping? - Svensson, Kerstin (Oñati Socio-Legal Series, 2023)
Advocacy is one of the central means for supporting access to justice. The social work profession has advocacy as one of its main courses of action. This discusses the components in actions that are considered as good practice for facilitating access to justice in its democratic aspects. More explicitly social workers advocacy for promoting the worth and dignity of human beings in society. Four different ideals in social work are presented, self-help, treatment, philanthropy and bureaucracy. Thereafter, cases presented as best practice from European social workers are used for pointing out the central components described for good advocacy work. These are communication, inclusion and flexibility. Taken together, the aspects all go back to having respect for those in need of advocacy. In advocating for access to justice, it is important that the advocates are actively aware of their own role in a way that their efforts facilitate access to justice.